2000
DOI: 10.2172/15002699
|View full text |Cite
|
Sign up to set email alerts
|

Results of 1999 Spectral Gamma-Ray and Neutron Moisture Monitoring of Boreholes at Specific Retention Facilities in 200 East Area, Hanford Site, Washington

Abstract: Twenty-eight wells and boreholes in the 200 East Are% Hanford Site, Washington were monitored in 1999. The monitored facilities were past-practice liquid waste disposal facilities and consisted of six cribs and nineteen "specific reterition" cribs and trenches. Monitoring consisted of spectral gamma-ray and neutron moisture logging. All data are included in Appendix B. '5U '8U and 154Eu were identified on speclral gamma logs from boreholes The isotopes 137Cs, '°Co, , , monitoring the PUREX specific retention f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A mass calculation was then applied to the plume, which assumed that all of the nitrate was in the pore fluid and an average volumetric water content of 0.085 cm3 ~r n -~. The water content was derived from the top 60 meters of the gravimetric water content from C4191 cores multiplied by a bulk density of 1.6 g ~r n -~ The total mass of nitrate calculated at the BC Crib was 2 Volume estimates of the resistivity plume showed that an isop@ between 163 ohm-metm and…”
Section: Figurementioning
confidence: 99%
“…A mass calculation was then applied to the plume, which assumed that all of the nitrate was in the pore fluid and an average volumetric water content of 0.085 cm3 ~r n -~. The water content was derived from the top 60 meters of the gravimetric water content from C4191 cores multiplied by a bulk density of 1.6 g ~r n -~ The total mass of nitrate calculated at the BC Crib was 2 Volume estimates of the resistivity plume showed that an isop@ between 163 ohm-metm and…”
Section: Figurementioning
confidence: 99%
“…Radiological and inorganic liquid waste was directly disposed into subsurface infiltration galleries, including 20 unlined cribs and six concrete‐lined trenches (DOE/RL, 2008), because it was hypothesized that contaminants discharged to the subsurface could be selectively retained through ion exchange, with radioactivity decaying over time (Gee et al., 2007). Several borehole geophysical studies (Brodeur et al., 1993; Fecht et al., 1977; Horton & Randall, 2000) and geologic, geochemical, and hydraulic measurements (Serne et al., 2009) were conducted to assess that contaminants had not reached groundwater. They found that there was ongoing but limited vertical migration to approximately 70 m below ground surface but concluded that contaminants did not reach the water table, reported at a depth of 104 m (Benecke et al., 2006).…”
Section: Introductionmentioning
confidence: 99%